POLITICS OF LANGUAGE IN THE ACT REGULATING MATTERS PERTAINING TO SPECIFIC AUTONOMY FOR PAPUA : Critical Discourse Perspective - Warami, Hugo; Mbete, Aron Meko; Putra Yadnya, Ida Bagus; Simpen, I Wayan (e-Journal of Linguistics, 2014)
This article aims to illustrate that the politics of language marked power relations framed by a form of power between the dominating and the dominated in the Act Regulating Matters Pertaining to Specific Autonomy for Papua (hereinafter called UU Otsus Papua ). The politics of language involves a high degree of knowledge and power that is marked by the symbolic interactions in the ethnic diversity of the archipelago UU Otsus Papua is a form of political discourse and the medium of language diplomacy containing an authority and political competence of the central government over the people of Papua; including a number of authorities and policies, as well as to explore the power of language in the language politics networks through the system of government of the Republic of Indonesia. Politics of language in this article will be disclosed through the paradigm of Critical Discourse Analysis (CDA). This article will focus on the efforts of uncovering: “Language Politics in UU Otsus Papua ”, by projecting the problems including: (i) the form of the politics of language, and (ii) the political function of language in the UU Otsus Papua .
Keywords: political language, Act, and specific autonomy for Papua